THE ROLE OF COMMUNICATION AFFORDANCES IN POST-TRAUMATIC STRESS DISORDER SUPPORT GROUPS ON FACEBOOK AND WHATSAPP - Yeshua-Katz, Daphna (AoIR Selected Papers of Internet Research, 2021)
Digital health research has highlighted the fact that people with stigmatized health problems are drawn to online support groups (OSG) because these groups help them to manage their stigmatized health conditions. However, little is known about how media affordances— the interaction between the technology and the user—reconfigure the ways in which stigmatized individuals use OSG and interact with others like themselves. The current study applied an affordance framework to evaluate how Facebook and WhatsApp support groups can help military veterans and their partners cope with posttraumatic stress disorder (PTSD) and was based on interviews with 34 PTSD OSG members in Israel. This research identified five affordances that members appraised to enhance their coping efforts in the digital world: visibility, availability, multimediality, surveillance, and synchronicity. This study reveals the connection between a specific stigmatizing mental health disorder (i.e., PTSD), perceptions of communication technologies (i.e., affordances), and specifies uses of technologies for coping with this mental health disorder. Moreover, this study may inform digital intervention designers about which communication affordances can potentially lead to better health outcomes.